Karyotype analysis of Kutsay. Allium odoratum L. (Alliales Alliaceae). - Bermejo, Jo-Am Asis
The C-metaphase count of Allium odoratum revealed that the chromosme number was 2n=32, consisting of the following centromeric groups based on Levan's method of chromosome classification: Group I chromosomes with subterminal centromeres (1pair); Group II with submedian centromeres (2pairs); and Group III with median centromeres (13pairs). The mean total lenghts of chromosome ranged from 8.534 0.054-16.624 0.600 u. Mitotic index for the species was found to be 10.87.